(untitled) (IJOVTECH, 2026)
The current study looked at prospective undergraduate students' preferences for specific courses based on their levels of mathematics anxiety. One hundred thirty-eight students in tertiary institutions participated in the research. The Math Anxiety Scale (MAS) was used to measure the respondent's level of math anxiety. Their subject choice was indicated in the demographic section. A linear regression analysis was conducted to examine the predictive effect of mathematic anxiety on the prospective student's course preference. The study showed that mathematic anxiety statistically significantly predicted the respondent's course preference F (1,136), 128.97, P<.000. Notably, the finding revealed that mathematics anxiety contributed to about 16.1% of the prospective undergraduate's course preference variation. Thus, the assumption that mathematic anxiety significantly predicts course preference among prospective undergraduates was true. The findings and practical implications of the study are discussed.